Dual‐Scale Nanomembranes: Ultrathin Dual‐Scale Nano‐ and Microporous Membranes for Vascular Transmigration Models (Small 6/2019). Issue 6 (8th February 2019) - Salminen, Alec T.; Zhang, Jingkai; Madejski, Gregory R.; Khire, Tejas S.; Waugh, Richard E.; McGrath, James L.; Gaborski, Thomas R.
Abstract : A new take on membranes for vascular modeling. In article1804111, James L. McGrath, Thomas R. Gaborski, and co‐workers lithographically fabricate dual‐scale (nano‐ and micro‐porous) membranes from ultrathin (100 nm) silicon nitride nanomembranes to support human endothelial cell culture for vascular modeling at the lab bench. Micropores provide transmigration routes for studying immune, cancer, and stem cell egress through the vascular wall.